2001
DOI: 10.1002/aqc.442
|View full text |Cite
|
Sign up to set email alerts
|

A review of marine protected areas in the northwestern Mediterranean region: siting, usage, zonation and management

Abstract: ABSTRACT1. We present in this review a general description of marine protected areas (MPAs) in the northwestern Mediterranean and some general principles for the establishment of protected areas, including their size, location, biotope composition, regulation, and management.2. Many Mediterranean MPAs are located around or adjacent to islands, but the placement of a marine reserve close to a large urban area is not necessarily a handicap, as has been demonstrated by some examples. It is not, therefore, necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 43 publications
1
111
0
8
Order By: Relevance
“…The greater species richness inside the Cerbère-Banyuls MPA (NO and R) than at OR-N is due to the presence of certain species like (Epinephelus marginatus, Sciaena umbra and Diplodus cervinus) that were encountered exclusively inside the marine re serve. This exclusivity is due to their high sensitivity to artisanal or recreational fishing pressure and their low production/ biomass ratio (Francour et al 2001, Lenfant et al 2003.…”
Section: Suitability Of Dov For Studying Reserve Effectmentioning
confidence: 99%
“…The greater species richness inside the Cerbère-Banyuls MPA (NO and R) than at OR-N is due to the presence of certain species like (Epinephelus marginatus, Sciaena umbra and Diplodus cervinus) that were encountered exclusively inside the marine re serve. This exclusivity is due to their high sensitivity to artisanal or recreational fishing pressure and their low production/ biomass ratio (Francour et al 2001, Lenfant et al 2003.…”
Section: Suitability Of Dov For Studying Reserve Effectmentioning
confidence: 99%
“…currents and distances). Reciprocally, when projects aimed at enhancing adult assemblages are devised (marine reserve, artificial reefs) they should be set next to or include nursery habitats in order to take advantage of the local adult reproductive potential (Francour et al, 2001).…”
Section: Coastal Management Implicationsmentioning
confidence: 99%
“…More recently, Coll et al (2004) and Chavoin and Boudouresque (2004) demonstrated the role of recreational spearfishing in the depletion of large fish from Mediterranean rocky reefs and Morales-Nin et al (2005) pointed out that 31% of the annual fish production at trophic level 4 is removed from the coastal waters of Majorca Island (Balearic Archipelago, western Mediterranean) by sport fishing. However, information about the relevance of recreational fishing in the Mediterranean is still scarce and limited to rocky bottoms (Sánchez Lizaso et al, 2000;Francour et al, 2001 and references herein).…”
Section: Introductionmentioning
confidence: 99%